Large perineal and gluteal angiomyxoma: the role of diagnostic imaging and literature review - Idrus Alhabshi, Sharifah Majedah (BMJ Publishing Group, 2013)
Aggressive angiomyxoma is a benign soft tissue tumour usually affecting the pelvis and perineum predominantly in women. Because of its variable presentation, this tumour is often clinically misdiagnosed as liposarcoma. We describe a case of a 38-year-old woman who presented with a large perineal and gluteal mass which increased in size in one year. Ultrasound showed hypoechoic mixed solid and cystic mass. Contrasted CT and MRI examinations showed typical appearance of swirling and layering pattern. She had undergone TAHBSO as the mass was difficult to dissect intra-operatively. The post-operative specimen confirmed to be an aggressive angiomyxoma.